Project-research approach in shaping the digital culture of future teachers of the natural science and mathematics cycle - Aliev, Emil (Educological discourse, 2026)
The article provides a theoretical and methodological substantiation of the project-research approach as a means of shaping the digital culture of future teachers of the natural science and mathematics cycle. The relevance of the study is determined by the need to overcome the fragmentation of teacher training, in which digital tools are often taught separately from subject methodology, assessment, and pedagogical decision-making. The author argues that the digital culture of a future teacher should be understood not as a set of isolated technical skills, but as an integrated professional quality manifested in the ability to design pedagogically meaningful digital solutions, work with educational evidence, interpret learning data responsibly, and continuously improve teaching practices. The study relies on theoretical analysis and synthesis of scientific sources, comparison of approaches, conceptual modeling, and generalization of methodological solutions relevant to STEM teacher education. The proposed framework integrates the logic of project-based learning, inquiry-based learning, TPACK, data literacy, and the ethical dimension of digital pedagogy. It is shown that the project-research cycle includes the following interrelated stages: formulation of a didactic problem, design of a digitally enriched solution, evidence planning, implementation, data analysis, and reflective redesign. Each stage is associated with specific artifacts, types of evidence, and quality criteria, which makes the process reproducible and pedagogically manageable. Particular attention is paid to scaffolding, assessment, ethical responsibility, and the methodological alignment of goals, content, methods, technologies, and evaluation. The article also proposes a typology of productive project formats for future science and mathematics teachers, including digital experiments, modeling projects, open data projects, integrated STEM cases, and digital assessment projects. It is concluded that the project-research approach enables the transition from learning digital tools to developing evidence-based, reflective, and ethically grounded professional practice.